Outcome and Prognostic Factors in Cats Undergoing Resection of Intestinal Adenocarcinomas: 58 Cases (2008–2020) - Czajkowski, Peter S.; Parry, Nicola M.; Wood, Carrie A.; Casale, Sue A.; Phipps, Whitney E.; Mahoney, Jennifer A.; Spector, Daniel I.; Price, Lori Lyn; Berg, John (Frontiers in Veterinary Science, 2022)
The purpose of this multi-institutional retrospective study was to expand the available data pertaining to pre-operative clinical findings, progression-free and overall survival times, and potential prognostic factors for cats undergoing surgery for intestinal adenocarcinomas. Fifty-eight cats treated over a 12-year period were included in the study. Progression-free and overall survival times were estimated using Kaplan-Meier analyses. Potential prognostic variables were evaluated for associations with progression-free and overall survival using univariate Cox proportional hazards regression analyses. Prior to surgery, the intestinal mass was identified using ultrasonography in 89% of cats in which it was applied; however, imaging findings suggestive of intrathoracic metastases were observed in only 9% of cats. Among 22 cats undergoing ultrasound-guided fine needle aspiration cytology, the results agreed with the results of histopathology in only 10 cats. Discordant results were most commonly related to the presence of marked inflammation in cytology samples, which may have obscured the presence of neoplastic cells. Diffuse intestinal small cell lymphoma was identified as a comorbidity in 5 cats. Resection of the tumor with the objective of obtaining wide surgical margins was performed in each cat. On histopathology, 20 tumors were classified as mucinous adenocarcinoma and 28 were adenocarcinoma not otherwise specified. Intestinal transection site margins were complete in 94% of cats; however, complete mural margins were present in only 15% of cats. Local lymph node metastases were identified in 52% of cats and carcinomatosis was diagnosed in 81% of cats. Disease progression was documented in 32 of the 58 cats (55%). Of these 32 cats, 14 (43%) had local recurrence of the primary intestinal tumor. Median progression-free survival was 203 days (95% CI 130-299days), and median overall survival time was 284 days (95% CI 200-363 days). Mitotic count was inversely associated with progression-free survival (HR 1.04; 95% CI 1.01-1.07, P=0.005); however, none of the remaining potential prognostic factors, including administration of adjuvant chemotherapy, were significantly associated with progression-free or overall survival. Feline intestinal adenocarcinoma remains an aggressive and highly fatal disease. Large, randomized controlled clinical trials will be needed to improve the survival prospects for affected cats.